SILICA EXPOSURE AND INTERLEUKIN-8 (IL-8) LEVELS OF MARBLE ARTISANS IN TULUNGAGUNG, INDONESIA - widajati, Noeroel; Kusuma Scorpia Lestari; Saliza Mohd Elias; Ari Prayogo Pribadi; Hadi Prayitno; Vivien How (Malaysian Journal of Public Health Medicine, 2026)
Working as a marble artisan exposes individuals to marble dust, which often contains high levels of silica. This study looks at how breathing in marble dust affects marble workers in Tulungagung. It focuses on respiratory problems and higher IL-8 levels in their blood, aiming to understand how much silica in the dust relates to these health issues. This cross-sectional observational study involved 30 artisans, assessing silica dust levels using personal dust samplers and IL-8 levels via ELISA. In Tulungagung, many marble artisans, mostly over 45 years old with over 5 years of experience, work 8 hours daily using cloth masks for protection. The finishing unit had the highest dust exposure, with levels far above safe limits: dust measured 37.1203 mg/m³ (TLV is 10 mg/m³), and silica concentration was 0.1114 mg/L (TLV is 0.0250 mg/L). The study found a clear relationship between using PPE, exposure to silica, reports of shortness of breath, and higher IL-8 levels in the blood (p < 0.05). The study showed that higher silica in marble dust is tied to increased IL-8 levels in the blood of marble artisans in Tulungagung. However, there was no clear link found between breathable dust levels and IL-8 in their blood.